المسيحية في شمال القفجاق حتى منتصف القرن الثامن الهجري / الرابع عشر الميلادي - مرعي، عماد كامل (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2023)
لم يحظى شمال القفجاق بما يكفي من البحث العلمي والدراسات الأكاديمية، التي من خلالها يمكن استيعاب تاريخ تلك المنطقة وتكوين صورة واضحة عنها، فمعظم الدراسات التاريخية الإسلامية وجهت اهتماماتها إلى المشرق أو المغرب الإسلاميين أو مركز الدولة الإسلامية، وتجنبت الاهتمام إلى حد ما بما يحدث في شمال العالم الإسلامي أقصد شمال القفجاق، علما أن تلك المناطق قد تأثرت بالدول المجاورة لها، واكتسبت حضارتها مما يحيطها من دول وخاصة الدولة الإسلامية والدولة البيزنطية دينيا واقتصاديا واجتماعيا وعلميا، وكانت على صلة بهم في شمال القفجاق بل وأثرت في مجرى تاريخهم، فكثير من الأحداث التاريخية التي مرت بها الدولة الإسلامية أو ندها الدولة البيزنطية، لا يمكن فهمها دون دراسة تاريخ دول وشعوب شمال القفجاق الواقعة على تخومهم. وقد سلط البحث الضوء على الجانب التاريخي للديانة للمسيحية في شمال القفجاق، منذ بداية انتشارها فيه، والكيفية التي انتشرت فيها وأهمية الموقع الجغرافي ودوره في قبول المسيحية بين دوله وشعوبه، فضلا عن أثرها في تغيير كثير من عادات وتقاليد وديانات تلك الدول والشعوب التي كانت تعيش في خضم الوثنية قبل وصول الديانات السماوية إليها، ودور الدولة البيزنطية ومحاولاتها المستمرة في نشر تلك الديانة، والتي نتج عنها استمالة الصقالبة والروس في اعتناقها بل وتوحيد الدولتين في دولة واحدة حكمها الروس وأصبحوا الراعي الرسمي للديانة المسيحية والمدافع عنها أمام المد الإسلامي، والذي أفشل مخططات الدولة البيزنطية في نشر المسيحية بين بقية دول وشعوب شمال القفجاق الأخرى المجاورة لدولة الروس، مثل دولة الخزر ودولة البلغار وشعب البجناك وغيرهم من القبائل الصغيرة في الجزء الشرقي من شمال القفجاق. The north of the Caucasus has not received sufficient scientific research and academic studies, through which it is possible to understand the history of that region and form a clear picture of it. Most Islamic historical studies directed their interests to the Islamic East or West or the center of the Islamic state, and avoided interest to some extent in what is happening in the north. The Islamic world, I mean the northern Qafqaq, knowing that those regions were influenced by their neighboring countries, and acquired their civilization from the countries that surrounded them, especially the Islamic state and the Byzantine state, religiously, economically, socially and scientifically, and they were connected to them in the northern Qafqaq and even influenced the course of their history, so many historical events What the Islamic State, or its counterpart, the Byzantine State, went through, cannot be understood without studying the history of the countries and peoples of the northern Caucasus located on their borders. The research shed light on the historical aspect of the religion of Christianity in the northern Caucasus, from the beginning of its spread there, the manner in which it spread, the importance of the geographical location and its role in accepting Christianity among its countries and peoples, as well as its impact in changing many of the customs, traditions and religions of those countries and peoples that lived in it, The midst of paganism before the heavenly religions reached it, and the role of the Byzantine state and its continuous attempts to spread that religion, which resulted in winning over the Slavic and Russians to embrace it and even unifying the two countries into one state ruled by the Russians. They became the official sponsor of the Christian religion and its defender in the face of the Islamic tide, which thwarted the plans of the Byzantine state. In spreading Christianity among the rest of the other countries and peoples of the northern Caucasus neighboring the state of the Russians, such as the state of the Khazars, the state of the Bulgars, the Pegnak people, and other small tribes in the eastern part of the northern Caucasus.
Keywords: الديانات السماوية -- الديانة المسيحية -- التاريخ الإسلامي